Precarious employment and health: A qualitative study in Venezuelan immigrant population in Colombia - Andrés A. Agudelo-Suárez; Mary Yanet Vargas-Valencia; Jonny Vahos-Arias; Gladys Ariza-Sosa; Wilder J. Rojas-Gutiérrez; Elena Ronda-Pérez (Elsevier, 2020)
Background: Employment and working conditions are considered as an element that impacts on health inequalities, especially among vulnerable groups such as the immigrant population. This study aims to describe the characteristics of precarious employment in the Venezuelan immigrant population in Medellín (Colombia) according to its theoretical model and its relationship with the perception of their physical, mental, and psychosocial health. Methods: A qualitative study was conducted with a focused ethnography perspective. 31 people with Venezuelan origin and work experience were interviewed in the city of Medellin and its metropolitan area and 12 key informants from different formal and informal social organizations that work with the immigrant population. A narrative content analysis was carried manually and by using the Atlas.Ti 8.0 software. The principles of analytical induction were applied to carry out a thematic analysis of the main categories defined in the precarious employment framework. Results: The following characteristics of precarious employment were found: instability in employment conditions, work in the informal or submerged economy, limited empowerment, absence of social benefits, high vulnerability, low income, and a limited capacity for exercising labor rights. This situation affects mental health conditions, access to health services, and the presence of risks due to the work they perform. Conclusions: The Venezuelan working population in Medellín is found in a precarious employment situation. Inclusive social strategies and policies that take into account the reality of this population are required.